Trans-oral incisionless fundoplication vs stretta, two recognized endoluminal anti-reflux therapies; a systematic review and meta-analysis - Obuobi, Reece-Bolton; Viswanath, Yirupaiahgari; Sathasivam, Rajeev; Bussa, Gopinath; Gill, Talvinder; Reddy, Anil; Shanmugam, Venkat; Gilliam, Andy; Thambi, Prem (International Surgery Journal, 2018)
Gastro-oesophageal reflux disease (GORD) is common with a prevalence of 10-20% in the Western World. During the last two decades, amongst introduced several endo-luminal techniques, evidence has emerged about the efficacy and safety of two treatment modalities for GORD; ’Stretta’ procedure and trans-oral incisionless fundoplication (TIF)’ or EsophyX. Author in this study aim to conduct a systematic review of published ’level 1’ evidence, to evaluate all evidence on the efficacy of Stretta procedure and TIF (EsophyX) for the management of GORD. A robust literature that included RCT trials only, searched on MEDLINE, EMBASE, and Cochrane library was undertaken from January 2007 until January 2017. The outcomes were normalisation of oesophageal pH values, augmentation of lower oesophageal sphincter pressure (LESP), health-related quality of life (HRQOL) score, and ability to stop or reduce PPI after procedure. For quality assurance purposes, two researchers were involved in the data collection process and its analysis. Author collected data from 9 RCT trials, 3 for Stretta and 6 for EsophyX. From the Stretta trials 101 patients were recruited, 92 patients were analyzed. Of the EsophyX trials, 3 of six papers were from single trial. A total of 296 patients were included and 203 were analysed. The pooled results show both stretta and esophyX significantly improved GORD symptoms. In a meta-analysis of trials, author found that both Stretta and EsophyX significantly improves GERD-HRQL score and enables patients to reduce or stop PPI intake compared with sham/PPI therapy alone. The overall quality of evidence is superior for EsophyX than it is for Stretta.